TENSE SHIFT AND RHETORICAL FUNCTION IN THE ABSTRACT SECTION OF SCIENCE JOURNAL BY NON-NATIVE SPEAKERS - Suharno, - (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
Abstract is an important part of scientific work for both seminar presentationÃÂ and journal publication in national or international level.ÃÂ Every writer is obliged to write an abstract for his/her publication.ÃÂ The aim of this study was to examine a number of abstracts in English scientific papers by non-native speakers (Indonesian lecturers).ÃÂ The study was focused on the linguistic and organizational features (i.e. tense shift and rhetorical function). The research results show that a number of abstracts in the data do not conform to the principles of abstract writing, that is some abstracts do not contain complete moves. In addition, the rhetorical shift is not always followed by the tense shift. ÃÂ Key words: abstract, tense shift, rhetorical function, move analysis